The Routledge handbook of nostalgia
1 online resource (xiii, 578 pages)
Keywords: "The Routledge Handbook of Nostalgia serves as a guide to the complex and often contradictory concept of nostalgia, as well as the field of "nostalgia studies" more broadly. Essential reading for students and researchers working in nostalgia studies, this book will also be beneficial to related disciplines such as philosophy, anthropology, geography, history and literature; cultural, media, heritage, museum and film studies courses; and more generally for readers interested in how the past is represented and used in the present"--